A century of mistakes in baseball - Berri, David J. (FT Press Delivers elements., 2010)
"This Element is an excerpt from Stumbling On Wins: Two Economists Expose the Pitfalls on the Road to Victory in Professional Sports (9780132357784) by David J. Berri and Martin B. Schmidt. Can sports decision-makers keep making the same mistakes for decades? Yes-and here's the proof"--Resource description page.